Drug-coated balloons versus 1ry stenting for TASC C and D femoropopliteal lesions - Ghoneim, Baker; Shaker, Ahmed; Karmoota, Ahmed; Abdelmola, Hany (International Surgery Journal, 2019)
Background: To compare the effectiveness and outcome of Drug-Coated Balloon (DCB) versus primary nitinol stenting for the treatment of long femoropopliteal lesions (TASC II C and D). Methods: This was retrospective study along 3 years included all the cases of femeropopliteal disease TASC C and D that was treated with DEB or primary stenting. The safety endpoint was 30-day free from major limb amputation and mortality. The primary end point was primary patency and freedom from clinically driven target lesion revascularization at 6 and 12 months, patient genders, demographics, co-morbidities, smoking history, indications for intervention were recorded. Results: PTA and post-dilation with paclitaxel-eluting balloons was done in 32 patients (group I) and 1ry stenting was done in 30 patients (group II) with either stenosis or occlusion. The mean lesion length was 18.43±2cm in group 1 and 18.8±2.32cm in group. The technical success rate was 100% in group II and 93.7% in group I. 6 months and 12-month patency rate for group I and II were 93.3% vs. 93.3% and 83.3% vs. 86.6%, respectively. There were no 30 days related major amputations or mortalities in either group. Conclusions: DCB for long femoropopliteal lesions showed a comparable result to primary stenting and provide durable results and lower incidence of target revascularization in patients with TASC C and D lesions.